Optimization of Energy Recovery Processes from Sunflower Stalks Using Expired Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) - Valentina Zubkova; Andrzej Strojwas; Stanislaw Baran (Energies)
The influence of the addition of expired paracetamol, naproxen, ibuprofen, and their blend on the course of pyrolysis of sunflower stalks was studied using the gravimetric technique as well as the techniques of IR and UV, XRD, and SEM and EDX spectroscopies. It was ascertained that ibuprofen has the highest effect in reduction of hydrocarbons in the composition of volatile pyrolysis products, which lowers the contribution of bands: saturated and unsaturated hydrocarbons by about 2.36 times; compounds with carbonyl groups by almost by three times; and the contribution of alcohols, phenols, and esters by 2.5 times in the FT-IR spectra. The reasons for a greater effectiveness of ibuprofen in reducing hydrocarbons in volatiles can be its lower temperature of decomposition and distinct composition of formed volatile pyrolysis products. Up to the temperature of 450 °C, paracetamol inhibits the migration of AAEMs from the pyrolyzed sample, the blend of pharmaceuticals accelerates the migration of all AAEMs except inorganics with Mg atoms. In the sediment of char of ibuprofen additive, there is a higher amount of Ca, Mg, and Cl atoms than in other chars, which can explain a greater influence of ibuprofen on the reduction of hydrocarbons in the composition of volatiles.